1999
DOI: 10.1088/0031-9155/44/2/018
|View full text |Cite
|
Sign up to set email alerts
|

A search for improved technique factors in paediatric fluoroscopy

Abstract: A Monte Carlo computational model of a fluoroscopic imaging chain was used for deriving optimal technique factors for paediatric fluoroscopy. The optimal technique was defined as the one that minimizes the absorbed dose (or dose rate) in the patient with a constraint of constant image quality. Image quality was assessed for the task of detecting a detail in the image of a patient-simulating phantom, and was expressed in terms of the ideal observer's signal-to-noise ratio (SNR) for static images and in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 38 publications
2
43
0
Order By: Relevance
“…It is suggested that the minimum number of images used should be at least 10 times the number of independent channels to provide a reliable estimate of the covariance matrix. 19 With 96 unique channels, at least 960 images are required to meet this recommendation. The frame rate of the system was set to 30 fps and four series of 10 s were saved.…”
Section: Phantom Construction and Image Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that the minimum number of images used should be at least 10 times the number of independent channels to provide a reliable estimate of the covariance matrix. 19 With 96 unique channels, at least 960 images are required to meet this recommendation. The frame rate of the system was set to 30 fps and four series of 10 s were saved.…”
Section: Phantom Construction and Image Acquisitionmentioning
confidence: 99%
“…6,10,11 Additionally, application of linear observer models to fluoroscopic and angiographic imaging systems has been investigated. [13][14][15][16][17][18][19][20][21][22][23][24][25][26] However, the vast majority of the reports feature investigations on simulated data. [13][14][15][16][17]19,[21][22][23][24][25] Although simulated data have significant merits for system design, data acquired from real imaging systems are required to assess real-world system performance.…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of image quality, including the aspect of minimising radiation exposure, is often carried out with the help of the concept of an image-quality figure (Gajewski and Reiss 1974;Thijssen et al 1989;Jennings et al 1993;Aichinger et al 1994;Tapiovaara et al 1999), which is sometimes derived from the SNR. Some examples are given in the following paragraphs.…”
Section: Other Image-quality Figuresmentioning
confidence: 99%
“…Tapiovaara et al have used the IQF to determine improved technique factors for paediatric fluoroscopy. The optimum technique was defined as the one that minimises the absorbed dose in the patient with a constraint of constant image quality (Tapiovaara et al 1999). …”
Section: Angiographymentioning
confidence: 99%